Potential Applications of Natural Coagulants in Portable Filtration Device for Flood Zone Residents - Hoang, Thi Tuyet Nhung (Journal of Technical Education Science, 2023)
Drinking water for residents who live in flood area is the concern of the government and environmental management. Using natural coagulants to transform flood water into potable water in order to reduce the number of chemical coagulants (aluminum salt) that have a negative impact on human health. The results of the flocculation procedure using agricultural residue extracts, dragon fruit branches (DFBE) and avocado seeds (ASE), did not meet the Vietnamese standard for the provision of potable water. Using DFBE and ASE as coagulation aides improves the flocculation efficacy of alum in high turbid water (150 to 175 NTU) and low turbid water (20 to 30 NTU). The ratio of ASE to Alum was determined to be 1/6 for high-turbidity water and 0.2 for low-turbidity water. The ratio of DFBE/Alum was determined to be greater than 1/3 for high turbidity water and less than 0.2 for low turbidity water. This ratio is also evaluated for a portable, simple, and user-friendly water filter that is suitable for flood-prone residents. Combining natural coagulation aides with Alum in water flocculation satisfies the Vietnamese standard with DFBE for sources with high turbidity and ASE for sources with low turbidity. This demonstrates the utility of natural coagulation aids derived from agricultural residues for water purification in flooded areas.